Ureolysis-induced calcium carbonate precipitation (UICP) in the presence of CO2-affected brine: A field demonstration. (July 2021) - Kirkland, Catherine M.; Akyel, Arda; Hiebert, Randy; McCloskey, Jay; Kirksey, Jim; Cunningham, Alfred B.; Gerlach, Robin; Spangler, Lee; Phillips, Adrienne J.
Highlights: UICP in the presence of CO2 -affected brine reduced injectivity in a wellbore cement channel by an order of magnitude. Ultrasonic imaging logs conducted after UICP treatment showed additional solids behind the casing which extended at least 30 m (100 ft) above the injection zone. Urease enzyme from heat-treated microbial cultures was an effective catalyst for UICP reactions. Abstract: Biomineralization is an emerging biotechnology for subsurface engineering applications like remediating leaky wellbores. The process relies on ureolysis to induce precipitation of calcium carbonate in undesired flow paths. In geologic storage of CO2, there is a potential for leakage and low pH conditions, thus, ureolysis-induced calcium carbonate precipitation (UICP) was tested at field scale to seal a channel in the wellbore cement annulus in the presence of CO2 -affected brine. Conventional oil field methods were used to deliver UICP-promoting fluids downhole to the treatment zone approximately 1000 feet (305 m) below ground surface (bgs). Over 4 days, 242 L (64 gal) of heat-treated Sporosarcina pasteurii cultures (22 bailers) and 329 L (87 gal) of urea – calcium chloride solution (30 bailers) were injected. The UICP treatment resulted in a 94% reduction of injectivity and ultrasonic well logging showed a noticeable increase in the percentage of solids in the channel outside the casing, including more than 30 m (100 ft) above the injection point. Subsequent well logging 11 months after the field demonstration showed that a significant portion of the new solids remained but the seal was compromised following sustained pumping. The results of this experiment suggest that UICP can be promoted in the presence of CO2 -affected brine to seal leakage pathways. Additional research is required to optimize long term seal integrity to ensure storage of CO2 in geologic carbon sequestration scenarios. Graphical abstract: Image, graphical abstract